Psychological well-being pada individu emerging adulthood: Bagaimana peranan fear of missing out dan kecanduan media sosial ? - Laily, Dita Rizqiatul; Santi, Dyan Evita; Ananta, Aliffia (SUKMA : Jurnal Penelitian Psikologi, 2024)
Abstract Emerging adulthood individuals are individuals who are quite diligent in using social media. In fact, according to several studies, excessive use of social media can have a negative effect on the level of psychological well-being due to fear of missing out and addiction to social media. This research aims to determine the relationship between fear of missing out and social media addiction with psychological well-being in emerging adulthood individuals. Using quantitative research methods with multiple analysis tests. Sampling using a purposive sampling technique involved 159 participants aged 18-25 years who actively use social media and live in Kebomas Gresik District. The results of the partial analysis of fear of missing out have a significant negative relationship with psychological well-being of -3.578 with p=0.000 (p<0.05), which means that if the level of fear of missing out is high, then the level of psychological well-being is low. Social media addiction also has a significant negative relationship with psychological well-being of -5.229 with p=0.000 (p<0.05) which means that if the level of social media addiction is high, then the level of psychological well-being is low. The results of the simultaneous analysis showed that fear of missing out and social media addiction together had an influence of 0.606 with p=0.000 (p<0.05) with an R2 value = 0.367, meaning that fear of missing out and social media addiction had a contribution of 36 .7% of psychological well-being in emerging adulthood individuals. Abstrak Individu emerging adulthood merupakan individu yang cukup rajin menggunakan media sosial. Padahal menurut beberapa studi, penggunaan media sosial yang berlebihan dapat memberikan efek negatif pada tingkat psychological well-being akibat adanya fear of missing out dan kecanduan media sosial. Penelitian ini bertujuan untuk mengetahui hubungan antara fear of missing out dan kecanduan media sosial dengan psychological well-being pada individu emerging adulthood. Menggunakan metode penelitian kuantitatif dengan uji anareg berganda. Pengambilan sampel menggunakan teknik purposive sampling melibatkan 159 partisipan usia 18-25 tahun yang aktif menggunakan media sosial dan berdomisili di Kecamatan Kebomas Gresik. Hasil analisis parsial fear of missing out memiliki hubungan negatif signifikan dengan psychological well-being sebesar -3,578 dengan p=0,000 (p<0,05) yang berarti jika tingkat fear of missing out tinggi, maka tingkat psychological well-being rendah. Kecanduan media sosial juga memiliki hubungan negatif signifikan dengan psychological well-being sebesar -5,229 dengan p=0,000 (p<0,05) yang berarti jika tingkat kecanduan media sosial tinggi, maka tingkat psychological well-being rendah. Hasil analisis simultan diketauhi bahwa fear of missing out dan kecanduan media sosial secara bersama-sama memberikan pengaruh sebesar 0,606 dengan p=0,000 (p<0,05) dengan nilai R2 = 0,367 artinya fear of missing out dan kecanduan media sosial memiliki kontribusi sebesar 36,7% terhadap psychological well-being pada individu emerging adulthood.